Electrical cardioversion to assess the association between self-reported symptoms and rhythm status in patients with persistent atrial fibrillation. (24th May 2021) - Hermans, ANL; Pluymaekers, NAHA; Lankveld, TAR; Van Mourik, MJW; Zeemering, S; Dinh, T; Den Uijl, DW; Luermans, JGLM; Vernooy, K; Crijns, HJGM; Schotten, U; Linz, D
Abstract: Funding Acknowledgements: Type of funding sources: None. Background. Knowledge about the association between symptoms and rhythm status (symptom-rhythm correlation) has potential clinical implications as it may identify patients with atrial fibrillation (AF) who profit from rhythm control in regard to reduction in symptom burden and improvement in quality of life. However, standardized strategies to assess symptom-rhythm correlation in AF patients are currently not available. Purpose. This study aimed to assess symptom-rhythm correlation in patients with persistent AF using electrical cardioversion (ECV) as a diagnostic probe. Methods. We used ECV to examine symptom-rhythm correlation in 81 patients with persistent AF. The presence of self-reported symptoms before ECV and at the first outpatient AF clinic follow-up visit (within 1-month) was assessed to determine the prevalence of a symptom-rhythm correlation (defined as self-reported symptoms present during AF and absent in sinus rhythm or absent in AF and yet relief during sinus rhythm). The symptom-rhythm correlation was absent in patients with symptoms before ECV who remained symptomatic during sinus or in patients with symptoms prior to ECV and without symptoms in AF after ECV. Asymptomatic patients before ECV with or without symptoms in AF or sinus rhythm afterwards had no symptom-rhythm correlation as well. The symptom-rhythm correlation was unevaluable in patients who were symptomatic in AF before ECV and at the first outpatient AF clinic follow-up visit. In addition, predominant self-reported symptoms (symptoms with highest self-reported symptom burden) were assessed to evaluate the symptom patterns around ECV. Intra-individually variable symptom patterns were defined as changes in predominant self-reported symptoms within patients around ECV. Results. Symptom-rhythm correlation was assessed in all patients. Only in 18 patients (22%), a symptom-rhythm correlation could be documented. Twenty-eight patients (35%) did not show any symptom-rhythm correlation and 35 patients (43%) had an unevaluable symptom-rhythm correlation as these patients were in symptomatic AF both at baseline and at the first outpatient AF clinic follow-up visit. Importantly, self-reported symptom patterns around ECV were intra-individually variable in 10 patients (12%) without symptom-rhythm correlation (of which 9 patients (11%) had AF recurrence) and in 2 patients (2%) with an unevaluable symptom-rhythm correlation. Conclusions. In patients with persistent AF, the prevalence of a symptom-rhythm correlation around ECV is low, but ECV often changes symptom pattern. Further studies are warranted to identify more optimal strategies to assess symptom-rhythm correlation in patients with persistent AF.